2015
DOI: 10.1128/iai.00858-15
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Vaccination with a Fimbrial Tip Adhesin and Passive Protection of Neonatal Mice against Lethal Human Enterotoxigenic Escherichia coli Challenge

Abstract: e Globally, enterotoxigenic Escherichia coli (ETEC) is a leading cause of childhood and travelers' diarrhea, for which an effective vaccine is needed. Prevalent intestinal colonization factors (CFs) such as CFA/I fimbriae and heat-labile enterotoxin (LT) are important virulence factors and protective antigens. We tested the hypothesis that donor strand-complemented CfaE (dscCfaE), a stabilized form of the CFA/I fimbrial tip adhesin, is a protective antigen, using a lethal neonatal mouse ETEC challenge model an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 51 publications
2
35
0
2
Order By: Relevance
“…Abundance of major subunits makes it easy for derived antibodies to target against adhesins, leading to effective protection against bacterial adherence and ETEC diarrhea. But recent studies suggested that adhesin tips play a key role in bacteria attaching to host receptors, and antibodies against tips are thought critical for protection against ETEC adherence and colonization [49, 50]. Data from this study indicated that antibodies derived from ETEC adhesin tips inhibited adherence of E. coli or ETEC bacteria expressing CFA/I, CS1-CS6, CS21 and EtpA to Caco-2 cells.…”
Section: Discussionmentioning
confidence: 68%
“…Abundance of major subunits makes it easy for derived antibodies to target against adhesins, leading to effective protection against bacterial adherence and ETEC diarrhea. But recent studies suggested that adhesin tips play a key role in bacteria attaching to host receptors, and antibodies against tips are thought critical for protection against ETEC adherence and colonization [49, 50]. Data from this study indicated that antibodies derived from ETEC adhesin tips inhibited adherence of E. coli or ETEC bacteria expressing CFA/I, CS1-CS6, CS21 and EtpA to Caco-2 cells.…”
Section: Discussionmentioning
confidence: 68%
“…Because ETEC cause disease while presumably being confined to the intestinal lumen, greater importance is placed on intestinal antibodies where abrogation of ETEC adhesion and colonization is tantamount to disease prevention. Elsewhere, however, we have shown that mouse vaccination with dscCfaE or CFA/I co-administered with an LT-based adjuvant elicited vaccine-specific coproantibody responses (37).…”
Section: Discussionmentioning
confidence: 99%
“…ADN y, recientemente, una mezcla celular completa inactivada de patotipos de E. coli [133][134][135][136][137] . Algunos de estos estudios están en la fase preclínica y otros con un grado de avance mayor en los estudios clínicos.…”
Section: Patogeniaunclassified
“…Los mayores avances en vacunas han sido en ECET. Se han investigado diferentes modelos con resultados variables en su efectividad, proteínas de algunos factores de virulencia expresados por ECET como CFs, subunidades de LT, ST, entre otros 133,137,138 . Para el control de las cepas de ECEP, desde hace varios años, con algunas de estas moléculas más conservadas, entre éstas la intimina, EspB, EspA y BfpA se han adelantado estudios para el desarrollo de vacunas en diversos modelos.…”
Section: Patogeniaunclassified